ANALISIS PENDAPATAN DAN SKALA USAHATANI JAGUNG DI DESA SINGGAMANIK KECAMATAN MUNTE KABUPATEN KARO - Christhoper Eka Trasta; Marlinda Apriyani; Teguh Budi Trisnanto; Sutarni Sutarni (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
This study aims to determine the level of income and the use of production factors on corn production in Singgamanik Village. This research was carried out from February 2021 to May 2021. Sampling used the slovin formula, which is a formula or formula to calculate the minimum number of samples if the behavior of a population is not known with certainty. Data analysis uses income analysis and Cobb-Douglass function analysis. The results showed that maize farming in Singgamanik Village was profitable and feasible to run because it had an R/C ratio of 2.37. The average income of corn farmers is Rp. 17,245,865 per hectare. Production factors of land area, seeds, urea, NPK, and pesticides have a simultaneous effect on corn production, while labor does not simultaneously affect corn production with a percentage of production variation of 97.5%. The corn production process in Singgamanik Village is at an increasing level of business (increasing return to scale), meaning that if an addition is made to the use of production factors, it will produce additional production with a larger proportion.